Analysis of Community Preparedness in Facing Disasters Following the Establishment of Village Disaster Preparedness Teams in Situmeang Hasundutan Village, North Tapanuli Regency - Simanjuntak, Bobby; Ketaren, Otniel; Tarigan, Fridalina; Manurung, Kesaktian; Sinaga, Janno (Open Access Health Scientific Journal, 2025)
Background: Disasters are unpredictable events that can occur suddenly at any time and in any place. In response, the Indonesian government has prioritised disaster preparedness through various programmes, one of which is the Disaster Resilient Village (Desa Tangguh Bencana/Destana) initiative by BNPB. Situmeang Hasundutan Village is among those designated as a Destana. This study aims to analyse the community’s preparedness for facing disasters following the formation of Destana in Situmeang Hasundutan Village, North Tapanuli Regency.Methods: This qualitative study employed a phenomenological approach and was conducted in Situmeang Hasundutan Village, Sipoholon Sub-district, North Tapanuli Regency, from September 2023 to April 2024. A total of seven informants participated in the study. Data were collected through in-depth interviews, observations, and documentation.Results: The findings revealed that the informants’ knowledge and attitudes towards disaster preparedness improved through consistent dissemination of information and socialisation. Disaster simulations have been conducted, supported by an effective disaster information management system, including hazard maps and evacuation routes. Preventive efforts, such as the preparation of medicines, were in place. The mobilisation of human resources, including village leaders, religious and traditional figures, and youth representatives (18 people in total), demonstrated strong community readiness.Conclusion: The implementation of Destana has significantly contributed to increasing disaster preparedness in Situmeang Hasundutan Village. It is recommended that the North Tapanuli BPBD conduct regular simulations and provide continuous support to Destana cadres. Community members are also encouraged to remain informed about earthquake disaster risks due to the village's vulnerable location.